Readiness to Learn English for Early Childhood - Sri Sumarni Sumarni; Machdalena Vianty; Windi Dwi Andika (LPPM Universitas Pahlawan Tuanku Tambusai, 2022)
Teachers need to understand the factors that influence the readiness of early childhood to learn their new language, especially English, to avoid inappropriate stimulation practices. This study aimed to examine early childhood English learning readiness factors based on relevant theories and research results. This research method was a qualitative literature review study. The literature review consists of 70 references related to the topic of early childhood English. This research method is a qualitative literature review study. As a result, children's readiness to learn is influenced by internal and external factors. Internal factors include cognitive abilities, mastery of the initial language, mastery of a new language, namely English, emotional maturity, and intrinsic motivation. At the same time, the external factors that influence include extrinsic motivation, family, social culture environment, and stimulation by playing.The novelty is to identify the influence of children's readiness factors in learning English both inside and outside the child. As a result, the teacher can consider the readiness of the child to avoid mistakes in introducing English as a new language for early childhood.